Evaluation of the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry Bruker Biotyper for identification of Penicillium marneffei, Paecilomyces species, Fusarium solani, Rhizopus species, and Pseudallescheria boydii - Chen, Ying-Sheng; Liu, Yen-Hung; Teng, Shih-Hua; Liao, Chun-Hsing; Hung, Chien-Ching; Sheng, Wang-Huei; Teng, Lee-Jene; Hsueh, Po-Ren (Frontiers in Microbiology, 2015)
We evaluated the performance of matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS), the MALDI Bruker Biotyper system (microflex LT; Bruker Daltonik GmbH, Bremen, Germany), on the identification of 50 isolates of clinically encountered molds, including Penicillium marneffei (n=28), Paecilomyces species (n=12), Fusarium solani (n=6), Rhizopus species (n=3), and Pseudallescheria boydii (n=1). The isolates were identified to species levels by sequence analysis of the internal transcribed spacer (ITS) regions using primers ITS1 and ITS4. None of the 28 genetically well characterized isolates of P. marneffei were identified as P. marneffei by MALDI-TOF MS, because P. marneffei was not present in either Bruker general library (DB 5627) or Bruker filamentous fungi library V1.0. However, the rate of accurate identification as P. marneffei (score value 2.000) was 85.7% based on newly-created database from one P. marneffei strain (NTUH-3370) by MALDI Biotyper system. Sequencing analysis of these 22 non-P. marneffei isolates of molds revealed seven Paecilomyces variotii, six Fusarium solani, four Paecilomyces lilacinus, and one each of Paecilomyces sinensis, Rhizopus arrhizus, Rhizopus oryzae, Rhizopus microspores, and P. boydii. Although all the seven P. variotii isolates, four of the six F. solani, two of the four P. lilacinus, and two of the three isolates of Rhizopus species, and the P. boydii isolate had concordant identification results between MALDI-TOF MS and sequencing analysis, the score values of these isolates were all of <1.700. This study indicated that the MALDI Bruker Biotyper is ineffective for identifying P. marneffei and other unusual molds because of the current database limitations. Therefore, it is necessary to continuously update the MALDI-TOF MS databases.